Efficient Shoot Organogenesis Using Leaf Disc and Nodal Explants of Passion Fruit (Passiflora edulis Sims) and Genetic Fidelity Assessment Using Sequence-Related Amplified Polymorphism (SRAP) Markers - Lydia K. Asande; Omwoyo Ombori; Evans N. Nyaboga; Richard O. Oduor (International Journal of Agronomy)
Passion fruit (Passiflora edulis (Sims)) is currently ranked third among fruit exports from Kenya and has great potential since the demand for both fresh fruit and processed juice is on a continuous increase. Passion fruit production in Kenya is constrained by a lack of healthy, clean planting material, poor seed viability, and low germination rates. To address this, the present study reports an in vitro plant regeneration protocol for passion fruit using leaf disc and nodal explants and genetic fidelity analysis of the regenerated plants. The highest number of shoot regeneration was obtained on Murashige and Skoog (MS) medium supplemented with 2 mg·L−1 6-Benzyl amino purine (BAP) (shoot induction medium). The multiplication of shoots was optimum in MS medium supplemented with 3 mg·L−1 BAP. To eliminate the requirement of an additional step of in vitro rooting, exogenous application of putrescine induced the formation and development of roots on nodal explants. Genetic fidelity analysis of the in vitro regenerated and macropropagated plants with that of the mother plant was carried out by sequence-related amplified polymorphism (SRAP) markers, and monomorphic banding profile for 80% of the regenerants confirmed the genetic uniformity of the in vitro regenerated and macropropagated plants. The in vitro regeneration system developed can be utilized for mass clonal propagation for the economic commercial exploitation of this important tropical fruit.